Expanding the notion of personal well-being during covid-19 campus closure in India: results from a mixed-methods study with members of higher education - Yeon, G.; Perumbilly, S.; Elangovan, N.; Awungshi, S.; Varghese, K.J. (Asia Pacific Journal of Educators and Education, 2024)
The COVID-19 pandemic has challenged lives globally in unprecedented ways. While numerous studies have discussed the impact of this pandemic on human lives, this descriptive study examined how this pandemic affected personal well-being (PW) for members of Indian higher education in the early phase of the pandemic in 2020 when there were no vaccines and remedies available. Research participants (n = 551) were faculty members, graduate students, and non-teaching staff in Indian higher education. At the time of data collection, when all campuses were closed, all participants were functioning in their roles in the academic communities via virtual platforms. This descriptive study, based on a mixed-methods research design with concurrent triangulation strategies, collected data from all regions of India. Resulting data identified and discussed the impact of the pandemic on six domains of PW in the life of participants: (a) self-care; (b) professional growth; (c) quality of interrelationship within the family; (d) relationships with significant others outside of the family; (e) process of experiencing/facing and addressing challenges; and, (f) relationship with spirituality/transcendental dimensions. The relevance of the last domain may be unique to Indian participants’ socio-cultural context and ethos. The findings and discussion explain how PW is a composite of all these six domains, and the pandemic expanded the notion of PW for the members of Indian higher education. Further, the findings also provided a general orientation on how educational leadership teams and institutions can enhance at least three specific dimensions of their community members and thus increase the likelihood of improving the quality of their professional and personal life. The findings may also have relevance for academic communities worldwide and inform clinicians working with members of academic communities, educational institutions, and policymakers. © Penerbit Universiti Sains Malaysia, 2024.
Keywords: Teacher leadership; dept.mft; distributed leadership; middle leaders; middle leadership; peer-reviewed; teacher leaders

Transitional Challenges in Technology Adoption among Academic Communities in Indian Higher Education Institutions - N, Elangovan; Yeon, Guydeuk; PERUMBILLY, SEBASTIAN; AWUNGSHI, SARAH HORMEILA (Journal of International Technology and Information Management, 2021)
Keywords: dept.mft; peer-reviewed

Desire on the Inside: Incarcerated bisexual women, identity, and human connection - Smoyer, Amy; Harvey, Rebecca (Queering Desire: Lesbians, Gender and Subjectivity, 2024)
Queering Desire explores, with unprecedented interdisciplinary scope, contemporary configurations of lesbian, bi, queer women’s, and non-binary people’s experiences of identity and desire. Taking an intersectional feminist and trans-inclusive approach, and incorporating new and established identities such as non-binary, masculine of centre (MOC), butch, and femme, this collection examines how the changing landscape for gender and sexual identities impacts on queer culture in productive and transformative ways. Within queer studies, explorations of desire, longing, and eroticism have often neglected AFAB, transfeminine, and non-binary people’s experiences. Through 25 newly commissioned chapters, a diverse range of authors, from early career researchers to established scholars, stage conversations at the cutting edge of sexuality studies. Queering Desire advances our understanding of contemporary lesbian and queer desire from an inclusive perspective that is supportive of trans and non-binary identities. This innovative interdisciplinary collection is an excellent resource for scholars, undergraduate, and postgraduate students interested in gender, sexuality, and identity across a range of fields, such as queer studies, feminist theory, anthropology, media studies, sociology, psychology, history, and social theory. In foregrounding female and non-binary experiences, this book constitutes a timely intervention.
Keywords: dept.mft; dept.swk; peer-reviewed

Handbook of LGBTQ-Affirmative Couple and Family Therapy - Harvey, Rebecca; Murphy, Megan J.; Bigner, Jerry J.; Wetchler, Joseph L. (Routledge, 2021)
This comprehensive second edition inspires therapists to utilize clinical work to pragmatically address intersectional oppressions, lessen the burden of minority stress, and implement effective LGBTQ affirmative therapy. A unique and important contribution to LGBTQ literature, this handbook includes both new and updated chapters reflecting cutting-edge intersectional themes like race, ethnicity, polyamory, and monosexual normativity. A host of expert contributors outline the best practices in affirmative therapy, inspiring therapists to guide LGBTQ clients into deconstructing the heteronormative power imbalances that undermine LGBTQ relationships and families. There is also an increased focus on clinical application, with fresh vignettes included throughout to highlight effective treatment strategies. Couple and family therapists and clinicians working with LGBTQ clients, and those interested in implementing affirmative therapy in their practice, will find this updated handbook essential.
Keywords: dept.mft

Collaborating with transgender youth to educate healthcare trainees and professionals: randomized controlled trial of a didactic enhanced by brief videos - Martin, Andrés; Celentano, Jillian; Olezeski, Christy; Halloran, Justin; Penque, Brent; Aguilar, Jemel; Amsalem, Doron (BMC Public Health, 2022)
In collaboration with members of the transgender and gender diverse (TGD) community, we created a didactic resource about the unique needs of TGD youth.
Keywords: Adolescents; Gender-diverse; Health; Health education; Mental health; Transgender; dept.mft; dept.swk; peer-reviewed

Well-Being and Prosperity: Multidirectional Disciplinary Interactions with Religion - Morais, M.; Karakunnel, J.J.; Perumbilly, S.; Yeon, G.; Rassendren, G. (Journal of Dharma, 2022)
Despite significant advancements in science and technology, religion continues to influence human lives. The twentieth-century perspectives from social sciences, influenced by the secular hypothesis, mainly highlight the negative influence of religion on human progress and practically ignore its influential and positive impact on various fields of knowledge/disciplines. In this paper, we have examined literature from politics, economics, and psychology to understand religion’s impact on these disciplines and vice versa. We find that religion’s contribution to human society in the 20th and 21st centuries has been mostly positive, especially in education, healthcare, social justice, economic growth, ethics, and initiatives for eradicating inequality and injustice. For instance, religion provides effective coping measures and strategies when humans face uncertainties and catastrophes and facilitate comfort, confidence, and emotional wellness. Further, we realised that (i) the contemporary research literature in social sciences generally highlights the interaction between religion and various fields of knowledge in a unidirectional way —i.e., religion influencing disciplines and not how disciplines influence religion, and (ii) that it fails to reveal a more complex multidirectional and circular relationship between religion and social sciences. This paper proposes ways to bring together social scientists and religious scholars to facilitate the much-needed discussion on the multidirectional relationship between religion and social sciences, thereby paving the way toward the well-being of individuals and social transformation. © 2022 Journal of Dharma: Dharmaram Journal of Religions and Philosophies (DVK, Bangalore),.
Keywords: and well-being; charitable giving; circularity; dept.mft; linearity; peer-reviewed; political participation; religion; sustainable development; ⛔ No DOI found

Sexual Identity Development and Heteronormativity - Harvey, Rebecca; Stone-Fish, Linda; Levatino, Paul (The Handbook of Systemic Family Therapy, 2020)
Sexual identity development has traditionally been theorized about from within heteronormative societies founded on patriarchal notions with links to misogyny, racism, and classism, among others. These forms of domination have constrained the way sexual identity has been conceived of, researched and written about within the mental health fields and limited the efficacy of clinical work with all people but especially sexual minorities and those who are gender non-binary. In this chapter the authors will deconstruct heteronormativity, examine the deleterious effect of it on mental health, and locate the influence of intersections of oppression on the field of SFT theory and in clinical work. An LGBTQI (lesbian, gay, bisexual, transgender, questioning, intersex) affirmative clinical framework developed from systems theory and queer theory will be outlined, and then a case study using the framework will be described.
Keywords: LGBTQI; dept.mft; dept.swk; family therapy; heteronormativity; marriage and family therapy; sexual identity; systemic family therapy